Fluid resuscitation in thermally injured pediatric patients - Marinov, Z; Kvalténi, K; Koller, J (Acta chirurgiae plasticae, 1997)
More than two-thirds of critical burns in special burn units are children. The burned child continues to represent a special challenge, since resuscitation therapy must be more precise than that for an adult with a similar burn. Children have a limited physiologic reserve and the pediatric fluid replacement therapy is based on the principle of separate calculation of physiological and pathological losses. We have reviewed the most widely accepted pediatric isotonic fluid protocols. All these protocols calculate for replacement of pathological losses with a need of 2 ml/kg/% BSAB (body surface area burn) or 4 ml/kg/% BSAB. We choosed the formulas of two Shriner's Burns Institutes--the Cincinnati and the Galveston Unit as representatives, and calculated the fluid therapy for model burn children weights of 10 kg, 30 kg with 20, 40, 60, 80% BSAB. The results of calculations where compared with physiologic parameters of children. In conclusions we could show, that the 4 ml/kg/% BSAB formulas do replace all theoretically predicted pathophysiologic losses due to burns. However, the 2 ml/kg/% BSAB formulas are more practical as a guideline for resuscitation of pediatric patients because of greater therapeutical range and better clinical response of children threatened by burn shock. It is important to remember that all formulas are only guides to fluid therapy, they should be modified according to individual needs and clinical status of the patient. Only successful restoring and maintaining perfusion pressures leads to optimal oxygenation of injured and noninjured tissues, which promotes spontaneous healing, prevents wound conversion, minimise bacterial colonisation, and prepares the injured areas for early grafting.
Keywords: Body Surface Area; Clinical Protocols; lidé; kojenec; věk při počátku nemoci; Resuscitation; povrch těla; klinické protokoly; předškolní dítě; Infant; Child; Fluid Therapy; Humans; tekutinová terapie; Burns; popálení; Child, Preschool; Age of Onset; dítě; resuscitace